2020
DOI: 10.3390/cells9041018
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses during Tumour Initiation: From Zebrafish Transgenic Models of Cancer to Evidence from Mouse and Man

Abstract: The zebrafish is now an important model organism for cancer biology studies and provides unique and complementary opportunities in comparison to the mammalian equivalent. The translucency of zebrafish has allowed in vivo live imaging studies of tumour initiation and progression at the cellular level, providing novel insights into our understanding of cancer. Here we summarise the available transgenic zebrafish tumour models and discuss what we have gleaned from them with respect to cancer inflammation. In part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 253 publications
0
11
1
Order By: Relevance
“…A direct connection between inflammation and cancer is that tissue injury, and the concomitantly produced inflammatory factors, promote cancer cell growth via dysfunction in chemokine and cytokine signaling [4]. It is known that some cancer types rely on inflammatory signals for their progression, angiogenesis, proliferation and survival, invasiveness and metastasis [5][6][7]. Therefore, targeting inflammation is a promising therapeutic option for those types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…A direct connection between inflammation and cancer is that tissue injury, and the concomitantly produced inflammatory factors, promote cancer cell growth via dysfunction in chemokine and cytokine signaling [4]. It is known that some cancer types rely on inflammatory signals for their progression, angiogenesis, proliferation and survival, invasiveness and metastasis [5][6][7]. Therefore, targeting inflammation is a promising therapeutic option for those types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Through exhaustive comparison of the human and zebrafish genome assemblies, it was found that 82% of disease-causing human genes have at least one zebrafish ortholog ( Howe et al, 2013 ). This level of conservation has led to the development of a wide array of cancer models in zebrafish ( Casey and Stewart, 2018 ; Hason and Bartůněk, 2019 ; Casey and Stewart, 2020 ; Elliot, 2020 ). Through the years of ongoing research, the pathological similarities of cancer and preservation of the immune components have also been well established between zebrafish and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, 1,000 new molecules are being isolated from marine organisms, many of which have complex molecular structure, contain many potentially bioactive groups with so far undetermined mechanism of action (Van Andel et al, 2018). Marine organisms are used not only to obtain biologically active combinations, but in some cases as experimental models with unique experimental properties that provide additional possibilities for modeling and studying the biology of cancer (Elliot et al, 2020). Active interaction between representatives of various directions of science, medicine and industry would allow an effective implementation of all the stages of obtaining the final pharmaceutical product from marine organisms starting from the moment of discovery to use in practiceidentification of combinations, determining their biological activity, chemical synthesis, development of methods of targeted transport, clinical trials, to introduction into production (Newman, 2016;Barreca et al, 2020).…”
Section: Discussionmentioning
confidence: 99%